Uso de macrófitas aquáticas como espécies fitorremediadoras no tratamento terciário de efluentes de laticínios - Camargo, João Vitor (Universidade Federal de São Carlos, 2025)
The possible environmental contamination by heavy metals (HMs), such as cadmium (Cd), lead (Pb), and chromium (Cr), has become recurrent due to the increase in anthropogenic activities when these do not meet the correct technical recommendations. Thus, in order to minimize the damage caused by irregular activities, phytoremediation emerges as an efficient and cost-effective technique in which plants are used for environmental decontamination. In this context, the aquatic macrophytes Pontederia crassipes (Mart.) Solms (arrowhead water hyacinth), Pistia stratiotes L. (water lettuce), and Salvinia auriculata Aubl. (giant salvinia) stand out, as they have remediation potential for inorganic organic pollutants present in water bodies. The dairy industry is present throughout the national territory, and when this industrial sector does not properly manage its waste before discharging it into water bodies, severe cases of contamination occur. Therefore, we tested the hypothesis that aquatic macrophytes have phytoremediation potential as a biotechnological tool in the tertiary treatment of dairy effluents contaminated with pollutants. Our objective was to evaluate the phytoremediation efficiency of macrophytes in water bodies contaminated by heavy metals. We adopted a completely randomized experimental design, consisting of the species P. crassipes, P. stratiotes, and S. auriculata cultivated in dairy effluents containing heavy metals (Cd and Pb). To achieve this, we conducted analyses of physicochemical parameters, total dry matter mass (DMM) to indicate good plant adaptation, and analyzed the concentrations of toxic elements in plant tissues to understand HM accumulation. The collected data were subjected to Tukey and Friedman tests, and after data processing, we created time series graphs for the analyzed variables. The literature reports the existence of a family of protein transporters called 'ZIP', which is involved in the transport of Fe, Zn, Mn, and Cd. Other proteins and transporters stand out and show affinities with divalent ions. We speculate that the transport of potentially toxic elements (PTE) occurs through high- to low-affinity systems (HATS and LATS, respectively). The PTE concentrations were not detrimental to the vegetative growth of the macrophytes, and we highlight their ability to "polish" the physicochemical parameters of the effluent, demonstrating the efficiency of these plants in adjusting the effluent quality before its discharge into water bodies. Therefore, we accept our initial hypothesis that aquatic macrophytes have phytoremediation potential as a biotechnological tool in water bodies contaminated with pollutants.
Use of aquatic macrophytes as phytoremediator species in the tertiary treatment of dairy effluents
Keywords: Bioacumulação; Efluentes; Fitorremediação; Metais Pesados; Effluent Polishing; Heavy Metals; Metal Bioaccumulation; Physicochemical Parameters; Plant Growth; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL